2019
DOI: 10.1007/s00701-019-03820-9
|View full text |Cite
|
Sign up to set email alerts
|

A case series of early and late cranioplasty—comparison of surgical outcomes

Abstract: Background Cranioplasty is an increasingly common procedure performed in neurosurgical centres following a decompressive craniectomy (DC), however, timing of the procedure varies greatly. Objectives The aim of this study is to compare the surgical outcomes of an early compared to a late cranioplasty procedure. Methods Ninety adult patients who underwent a prosthetic cranioplasty between 2014 and 2017 were studied retrospectively. Timing of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
(57 reference statements)
4
26
0
1
Order By: Relevance
“…Firstly, patients diagnosed with DOC within 3 months may have a better natural prognosis, and secondly, early CP may provide benefits to consciousness recovery. Previous studies and systematic reviews have found that the benefits of improved nervous system function were greater with early (≤90 days) compared with late surgery (>90 days) (3,19), whereas the greatest improvement in cognitive function was noted when CP was performed within 3 to 6 months after DC (20). The reported incidence of complications in early and late CP remains controversial.…”
Section: Timing Of Surgerymentioning
confidence: 98%
“…Firstly, patients diagnosed with DOC within 3 months may have a better natural prognosis, and secondly, early CP may provide benefits to consciousness recovery. Previous studies and systematic reviews have found that the benefits of improved nervous system function were greater with early (≤90 days) compared with late surgery (>90 days) (3,19), whereas the greatest improvement in cognitive function was noted when CP was performed within 3 to 6 months after DC (20). The reported incidence of complications in early and late CP remains controversial.…”
Section: Timing Of Surgerymentioning
confidence: 98%
“…However, other studies have shown that super early CP can shorten the operation time, reduce intraoperative blood loss, and improve the neurological function and prognosis. 15 The above-mentioned meta-analysis by Malcolm et al., 16 which is the most recent to date, also demonstrated that super early (<90 days) CP significantly improved the prognosis of neurological function. Bender et al.…”
Section: Discussionmentioning
confidence: 93%
“…In their retrospective study, Bjornson et al compared early cranioplasty (33-90 days interval) with late cranioplasty (more than 90 days interval) and found no statistical difference between the two in complication rates. 37 In a retrospective study on 108 cases of cranioplasty by Ernst et al 31 in which subcutaneous bone flap storage was done, the mean time to cranioplasty was 104.31 days. However, they did not study the correlation between the bony union and the interval between the primary surgery and cranioplasty.…”
Section: Discussionmentioning
confidence: 99%